Implementation of Expository Learning Model to Enhance Learning Outcome in Islamic Cultural History on the Theme of Hijrah Para Sahabat Nabi SAW to Abyssinia - Asyari, Hobir; Pratiwi, Inne Marthyane (Al-Aulad: Journal of Islamic Primary Education, 2023)
This study aims to improve learning outcomes in Islamic Cultural History (SKI) for fourth-grade students, focusing on the theme of Hijrah Para Sahabat Nabi SAW to Abyssinia. The research method employed is Classroom Action Research (CAR). The study begins with the observation of unsatisfactory learning outcomes and the inability to reach the Minimum Mastery Criteria (KKM). Expository learning method is utilized, starting with material comprehension and viewing short films to enhance understanding. The teacher, aided by colleagues, conducts observations throughout the sessions. Evaluation, both oral and written assignments, is provided, followed by reflective sessions with students to summarize the learning. Numeric assessment is done based on the predetermined KKM standard. If initial results show less than 30% mastery, the process enters Cycle 2, maintaining the same material but with enhanced teaching strategies. If there's still insufficient progress, Cycle 3 is initiated, repeating the process until satisfactory results are achieved, with the aim of ensuring at least 90% of students meet the KKM standard.